Boosting Sustainability through Digital Transformation’s Domains and Resilience - Hajishirzi, Reihaneh (2022)
Hajishirzi, R., Costa, C. J., & Aparicio, M. (2022). Boosting Sustainability through Digital Transformation’s Domains and Resilience. Sustainability (Switzerland), (Special Issue Digitalization, Innovation and Sustainability), 1-15. [1822]. https://doi.org/10.3390/su14031822 ---------------------- Funding: The authors acknowledge financial support via ADVANCE-CSG from the Fundação para a Ciência and Tecnologia (FCT Portugal) through research grant number UIDB/04521/2020, and we gratefully acknowledge the financial support from FCT—Fundação para a Ciencia e Tecnologia, I.P., (Portugal), national funding through research grant UIDB/04152/2020—Centro de Investigação em Gestão de Informação (MagIC).